Global politics - Heywood, Andrew; Whitham, Ben (London ; New York, N.Y. : Bloomsbury Academic, 2023)
"A systematic and integrated analysis of the theory and practice of contemporary international relations, covering traditional and critical theory, core issues and recent developments in the field"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: International relations; World politics